Long-term Vipassana meditation enhances executive function in adult meditators - Thawatchai Lukseng (2020)
© 2020 Faculty of Medicine Siriraj Hospital, Mahidol University. Objective: Vipassana meditation (VM) is a traditional Buddhist meditation practice that focuses on monitoring of clear awareness of oneself exactly what is happening as it happens, without judging. Executive functions (EF) are the high-level cognitive processes that facilitate goal-directed behaviors. It is well known that VM has significant effects on various affective states of the mind, such as relaxation, reduce stress and anxiety; however, less is known about the effect of VM on the executive function. This study aims to examine the effects of VM practice on the performance of the executive function in the adult meditators. Methods: Forty adult participants, age range between 25-50 year-olds, were recruited to this study. They were divided into three groups; the control group (N=20, mean age = 40.5 ± 5.8 years), Short-term VM group (N=6, mean age = 38.0±9.1 years), and Long-term VM group (N=14, mean age = 37.7±7.3 years). All participants were examined by 1) State-trait anxiety inventory (STAI); 2) Philadelphia mindfulness scale (PHLMS); 3) Digit span task of WAIS-IV, 4) Tower of Hanoi (ToH), and 5) Wisconsin Card Sorting Test (WCST-CV4). The mean scores of all task performance were statistically analyzed and compared between groups. Alpha values of .05 were considered significant throughout. Results: Both short-term and long-term VM has common benefits to decreased anxiety and increased mindfulness score as compared with the non-meditator group. Although short-term VM shows some benefits to the performance of several EF tasks, the discrepancy was not significant when compared with the control group. In contrast, long-term VM had a significant benefit to the performance of working memory, planning, and shift/cognitive flexibility, when compared with the non-meditator group. Our results indicated that long-term VM practice not only reduces anxiety and improves mindfulness, but the benefit also extends to improve the performance of the executive function in adult practitioners. Conclusion: In conclusion, our results suggest that continued practice of VM is highly effective for enhancing EF in healthy individuals. Long-term VM practice not only reduce stress and improve mindfulness but also enhance the performance of EF tasks of the practitioners.